Faktor Keperilakuan Organisasi Terhadap Kegunaan Sistem Akuntansi Keuangan Daerah - Muhammad Imran Kalam; Syaikhul Falah; Rudiawie Larasati (Jurnal Akuntansi dan Keuangan Daerah, 2022)
This study aims to examine the influence of organizational behavioral factors (training, clarity of purpose and superior support) on the usefulness of regional financial accounting systems. The population of this study were all civil servants at the Jayapura Regency Regional Financial and Asset Management Agency. The sample used in this study were civil servants who had the authority to manage regional financial reports at the Jayapura Regency Regional Financial and Asset Management Agency office, with a total of 34 employees. This type of research is quantitative. Methods of data collection using a questionnaire / questionnaire. The data analysis method used is descriptive analysis. The results of the study show (1) there is a positive and significant effect of training on the use of the regional financial accounting system, (2) there is a positive and significant effect on the clarity of objectives on the use of the regional financial accounting system, (3) there is a positive and significant effect of superior support on the use of the accounting system regional finance.